A closer look at personal values and delinquency - Borg, Ingwer; Hermann, Dieter; Bilsky, Wolfgang (Personality and individual differences, 2017)
The paper takes a closer look at the relations of personal values and delinquency in two representative German surveys. A new definition for value items is proposed and used to cull 30 items that measure eleven basic values. It is shown that the structure of the values and their items in multi-dimensional scaling and in unfolding, respectively, suggest an underlying continuous value scale where the values are but verbal markers for different segments of the circle. This value circle is shared by almost all persons, and different persons differ only in terms of how they prioritize the various values. Centering or not centering the ratings leads to virtually the same value circles. The value circle allows predicting a sine-like pattern of correlations of values with attitudes on delinquency, self-reported delinquent behavior, and the perceived risks of delinquency. The best predictors are hedonism and stimulation (for positive relations towards delinquency) and tradition, conformity, and peace of mind (for negative relations).
Gesehen am 17.04.2018